Inspired by Surya Prakash

Calculus Level 3

1 × 2 a + 2 × 3 a 2 + 3 × 4 a 3 + 4 × 5 a 4 + \large \dfrac {1 \times 2}{a} + \dfrac {2 \times 3}{a^2} + \dfrac {3 \times 4}{a^3} + \dfrac {4 \times 5}{a^4} + \ldots

Find the value of the above expression provided a > 1 |a|>1 and if it continues ad infinitum.


2 a 2 ( a + 1 ) 3 \dfrac {2a^2}{(a+1)^3} 2 a 2 ( a 1 ) 3 \dfrac {2a^2}{(a-1)^3} 2 ( a + 1 ) 2 a 3 \dfrac {2(a+1)^2}{a^3} 2 ( a 1 ) 2 a 3 \dfrac {2(a-1)^2}{a^3}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

We first note that n = 0 x n = 1 1 x \displaystyle\sum_{n=0}^{\infty} x^{n} = \dfrac{1}{1 - x} for x < 1. |x| \lt 1.

Differentiating both sides, (the LHS term-by-term), gives us that

n = 1 n x n 1 = 1 ( 1 x ) 2 . \displaystyle\sum_{n=1}^{\infty} nx^{n - 1} = \dfrac{1}{(1 - x)^{2}}.

Differentiating once again gives us that

n = 2 ( n 1 ) n x n 2 = 2 ( 1 x ) 3 n = 2 ( n 1 ) n x n 1 = 2 x ( 1 x ) 3 . \displaystyle\sum_{n=2}^{\infty} (n - 1)nx^{n - 2} = \dfrac{2}{(1 - x)^{3}} \Longrightarrow \sum_{n=2}^{\infty} (n - 1)nx^{n - 1} = \dfrac{2x}{(1 - x)^{3}}.

Now since a > 1 |a| \gt 1 we have that 1 a < 1. \dfrac{1}{|a|} \lt 1. So plugging in x = 1 a x = \dfrac{1}{a} yields that

n = 2 ( n 1 ) n a n 1 = 2 a ( 1 1 a ) 3 = 2 a 2 ( a 1 ) 3 . \displaystyle\sum_{n=2}^{\infty} \dfrac{(n - 1)n}{a^{n - 1}} = \dfrac{\dfrac{2}{a}}{\left(1 - \dfrac{1}{a}\right)^{3}} = \boxed{\dfrac{2a^{2}}{(a - 1)^{3}}}.

Nice solution. +1

Sharky Kesa - 5 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...